Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament Dengan Media Number Card Terhadap Penguasaan Mufradat - Novita, Novita; Taubah, Miftachul; Syaifullah, Syaifullah (STIQ Amuntai, 2024)
The purpose of this study was to determine how effective the cooperative learning model using Team Games Tournament with the help of Number Cards on students' mastery of mufradat in class X A Madrasah Aliyah. With the subject matter of